2019
DOI: 10.1093/pm/pnz167
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture for Chronic Discogenic Sciatica, a Randomized Controlled Sham Acupuncture Trial

Abstract: Objective To evaluate the efficacy and safety of acupuncture for discogenic sciatica. Design Single-center, parallel, randomized controlled sham acupuncture trial. Methods Twelve sessions of acupuncture or sham acupuncture at the same traditional acupoints over four weeks. The primary outcome was change from baseline in weekly mean leg pain, measured by the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 21 publications
0
56
0
2
Order By: Relevance
“…Two recent trials provided restricted evidence in favor of acupuncture but both were conducted in single center with small sample sizes [29,30]. Generalization of these study results might be limited.…”
Section: Discussionmentioning
confidence: 91%
“…Two recent trials provided restricted evidence in favor of acupuncture but both were conducted in single center with small sample sizes [29,30]. Generalization of these study results might be limited.…”
Section: Discussionmentioning
confidence: 91%
“…A single-center, parallel, randomized controlled trial involving 46 patients with sciatica pain for at least 12 weeks found that acupuncture was safer than sham acupuncture in treating chronic sciatica and had a curative effect in improving short-term pain. 22 Two systematic reviews (one included 12 RCTs, 1842 patients; another included 11 RCTs, 932 patients) showed that acupuncture might be more effective in treating sciatica than drug therapy in relieving leg pain. 23,24 Pain is the most common symptom of sciatica.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] ACU stimulates blood circulation at corresponding acupoints thereby relieving pain, which is also the basis for ACU to treat pain caused by LDH. [ 21 ] From the current point of view, there are no sufficient evidence for ACU therapy of LDH as the relevant comprehensive research is still blank. The study aims to explore the potential relationship of treatment and safety between the effectiveness of ACU and LDH by conducting a systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%